The Role of Total Quality Management Systems in Enhancing Patient Safety and Infection Control: A Systematic Review - Sameer Alharbi, Abdulaziz Saleh; Owaid Eid Alanazi, Abdulaziz; Obaid Almutairi, Obaid Owaidh; Ibrahim Alsultan, Ali Mohammed; Gharib Alharbi, Mana Sameer Bin; Jaber Alwadani, Mohammed Ahmed; Safer S Almotairi, Mohammed; Bin Saud Alharbi, Meshari Saeed; A Alobaid, Fawaz Fahad; Lewaifi Alharbi, Mohammad (Journal of Neonatal Surgery, 2026)
Introduction: The Saudi Vision 2030 has encouraged the healthcare sector in the Kingdom to embrace Total Quality Management (TQM) as a philosophy of transformation in order to be in tandem with the worldwide safety and quality standards of clinical services. This strategy focuses on organization change of culture, leadership dedication and continuous process enhancement to reduce the harm that can be prevented. Study Objective: This systematic review aims to evaluate the importance of TQM systems for improving patient safety and preventing infection within Saudi Arabian health care organizations. This review will also look at synthesizing the current evidence for the adoption of TQM frameworks within Saudi Arabian hospitals and healthcare facilities. Methodology: The systematic review consolidated the information about the application of Saudi Central Board for Accreditation of Healthcare Institutions (CBAHI) standards, the Essential Safety Requirements (ESR) and specialized quality strategies such as Lean Six Sigma (DMAIC). The contribution of digital surveillance platforms, including the Health Electronic Surveillance Network (HESN), to the achievement of data-driven safety outcomes. Conclusion: The evidence suggests that the introduction of TQM is strongly linked to better hospital performance, which has resulted in clinical success (a 48.8% decrease in central line-associated bloodstream infections, or CLABSI) and major decreases in medication errors.6Although national accreditation has standardized safety processes, high staff turnover, resource limitations, and challenges in engaging clinical staff often disrupt sustained excellence.